Similarities in Southern African Development Community (SADC) Exchange Rate Markets Structure: Evidence from the Ensemble Empirical Mode Decomposition. Issue 2 (3rd April 2022) - Adam, Anokye M.; Kyei, Kwabena; Moyo, Simiso; Gill, Ryan; Gyamfi, Emmanuel N.
ABSTRACT: The need for exchange markets coordination in Africa is rooted in the quest of most economic blocs to form a monetary union characterized by a single currency and has therefore attracted the attention of researchers. The intrinsic complexity of the exchange rate market hinders researchers from producing consistently good results. The empirical mode decomposition (EMD) is a data-driven signal analysis method for nonlinear and nonstationary data. Empirical mode decomposition method can be used to divide nonlinear signal sequences into a group of well-behaved intrinsic mode functions (IMFs) and a residue, so that we can compare the similarities. In this paper, EMD and ensemble empirical mode decomposition (EEMD), a modified version of EMD, are applied to the exchange rate market of the Southern African Development Community (SADC). Through analyzing the intrinsic mode functions (IMFs) of EMD and EEMD, we find the EEMD method to perform better on the orthogonality of IMFs than EMD. We propose a new way of analyzing short and long-run comovement through the analysis of the characteristics of IMFs and residue. The analysis of the IMFs and residue obtained from EEMD showed that exchange rate markets in SADC are driven by economic fundamentals and 12 out of 15 countries examined showed some level of similarity in the long-term trend. Our findings have implications for the direction of future SADC monetary union.